More mobility, less traffic in case of inner-city development before expansion outwards - Topp, Hartmut (Raumforschung und Raumordnung | Spatial Research and Planning, 2003)
Inner-city development uses available infrastructure: The capacities suffice in case of a small-scale development or if other traffic-intensive uses are replaced—especially if the population decreases. They are not sufficient in case of large-scale inner-city developments. Following an „intermediary peak” in the last decade, new urban districts in the surrounding areas are not cosistent anymore with the emerging demographic development. Traffic remains a problem for intermediate city and suburbia: it is too dispersive for local public transport, the distances are too large to go by bicycle and foot. The dependence on the car binds a considerable part of budgets. Inner-city development benefits from the proximity to already available uses. The way in which mixed land use is individually handled, determines traffic-related effects. The related (controversial) discussion will be presented in the following.